Residential Wiring for the Trades - Stauffer H.Brooke (McGraw -Hill, 2005)
H. Brooke Stauffer's Residential Wiring for the Trades is intended to provide practical instruction for wiring homes according to NEC rules. This text covers all important topics and yet, won't scare students away with extensive detail and complexity. Written with apprentice students in mind, this four-color text covers all 2005 NEC requirements and construction practices for installing electrical systems in new one- and two-family dwellings. Using a unique, hands-on approach that will serve students well in the real-world, this text covers all aspects of the curriculum, introducing student-friendly applications to increase comprehension, many practical examples, extensive safety coverage, and introduction to the newest technology in residential wiring.